Solidarity in transboundary flood risk management: A view from the Dutch North Rhine–Westphalian catchment area. (3rd April 2017) - Van Eerd, Marjolein C.J.; Wiering, Mark A.; Dieperink, Carel
Abstract : Climate change is putting pressure on water systems, and its effects transcend man-made boundaries, making cooperation across territorial borders essential. The governance of transboundary flood risk management calls for solidarity among riparians, as climate change will make river basins more prone to flooding. 'Solidarity' means that individuals act to support members of a particular community to which they belong. Recently, the solidarity principle has become institutionalized due to its formalization in the EU Floods Directive. However, it is not clear what solidarity means in the upstream–downstream practices of transboundary flood risk management. Understanding the meaning of solidarity is important for the development of cross-border climate adaptation governance. This article discusses the conceptualization of the solidarity principle and explores its meaning for international cooperation in the Dutch North Rhine–Westphalian border region. Our critical case study reveals that although all actors understand the importance of solidarity, they interpret it differently, often based on self-interest related to their position in the catchment. The formal inclusion of the solidarity principle in the Floods Directive can best be seen as a step in the continuous development of transboundary flood risk governance, as no striking changes in practice have been identified after its formalization. Policy relevance As climate change increasingly puts pressure on river basins and other shared resources, cross-border cooperation and solidarity are seen as increasingly important. This article discusses the meaning of solidarity in practice and reveals how this normative principle may contribute to transboundary climate adaptation governance. Understanding its meaning is important for future cross-border climate adaptation governance.